Airway obstruction from tracheostomy balloon cuff herniation during oral cancer removal. Emergency successfully managed and lessons learnt from device malfunction. (February 2021) - Pandolfini, Manlio; Di Stadio, Arianna; Brenner, Michael J.; Pichi, Barbara; Pellini, Raul; McGrath, Brendan; D'Ascanio, Luca
Highlights: Trachestomy rigid tube could present same malfunction of flexible endotracheal tube. Malfunction can happen even in case of device check before insertion in the tracheostome. Sudden fall of oxygen saturation can be due to cannula malfunction during surgery. Prompt and rapid management of the device can safe patients' life. Abstract: Objective: Tracheostomy tube cuff balloon herniation is a rare event and can determine airway obstruction. Sometimes the obstruction is not very evident but, if it is not correctly solved, can determine a severe hypoxia with patient's death. Material and methods: We present a 49-year-old male patient, with cT4aN0M0 squamous cell carcinoma of the oral cavity, who was admitted to the hospital for definitive surgical resection. Due to mass an endo-oral intubation was not possible, so a surgical tracheotomy was performed. General anaesthesia was induced with Propofol (2 mg/kg) and Fentanil (1 mcg/kg) without gas. Surgery commenced via a trans-oral and trans-cervical approach, but it was halted after approximately 2 min as oximetry demonstrated a progressive fall from 98% to 78%. After confirmation of correct function of anaesthetic devices, the endotracheal cannula was tested; although surgeon deflated the tube cuff, repositioned the tube, and re-inflated the cuff, oxygen saturation did not change. So, the cannula was changed and patient's saturation increased up to normal value. Results: The balloon cuff of the cannula showed a herniation, responsible of insufficient ventilation. Conclusions: Cuff herniation should be considered in case of unexpected airway obstruction, and a systematic, rapid approach to investigation and management should ensure timely identification and correction.